2013
DOI: 10.1097/mcg.0b013e31827fd4a2
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Ulcerative Colitis Associated With Autoimmune Pancreatitis

Abstract: AIP patients seem to have a higher risk of UC compared with the general population. The increased IgG4-positive cellular infiltration in the colonic tissue suggests that UC may be an extrapancreatic manifestation of AIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
57
4
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 46 publications
6
57
4
5
Order By: Relevance
“…Finally, regarding AIP, it was found that its frequency in patients with IBD is 0.04%; this value was lower than the 0.4% previously reported [4,5] but was similar to that reported in a study carried out in the United States [6] . The reason for this could have been due to the underdiagnosis of AIP because it is not routinely investigated.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Finally, regarding AIP, it was found that its frequency in patients with IBD is 0.04%; this value was lower than the 0.4% previously reported [4,5] but was similar to that reported in a study carried out in the United States [6] . The reason for this could have been due to the underdiagnosis of AIP because it is not routinely investigated.…”
Section: Discussioncontrasting
confidence: 49%
“…Regarding autoimmune pancreatitis (AIP), the overall reported prevalence of this disease in IBD patients is approximately 0.5% in the Asian population [4,5], whereas in western countries and specifically in the United States, it is much lower [6] . Thus, the purpose of this study was to assess the frequency of benign pancreatic diseases, that is, acute pancreatitis, chronic pancreatitis (CP), and AIP, in a population with IBD treated in our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Gallstones and alcohol abuse are also long-established risk factors for acute pancreatitis[12]. The relationship between IBD and autoimmune pancreatitis (AIP) is mainly confined to UC[13,14]. Several studies have reported positive associations between risk for acute pancreatitis and IBD severity[15-17].…”
Section: Introductionmentioning
confidence: 99%
“…Although Ravi et al11 reported infiltration of IgG4-positive cells in the colonic mucosa of one patient with AIP and UC, and concluded that IBD might represent an extrapancreatic manifestation of AIP, whether this AIP was type 1 or type 2 was unclear. Park et al24 reported that six cases (5.8%) of the 104 AIP patients were diagnosed with UC, and two cases (33.3%) showed increased infiltration of IgG4-positive plasma cells into the colonic mucosa, but none with UC only. They hypothesized that UC may be an extrapancreatic manifestation of AIP.…”
Section: Discussionmentioning
confidence: 99%